Choujin X. Volume 9 - Ishida, Sui (Viz signature., 2025)
"Best friends Tokio and Azuma do everything together, even if most of the time it feels like Tokio is just stumbling along in Azuma's cooler, more talented footsteps. But when they're attacked one night by a superhuman mutant called a choujin, Tokio finally has a chance to shine--by turning into a choujin himself! Tokio's recent side quest to rescue Palma Shishinegura turns out to have been worth the effort when she's able to help them with a little problem--Yamato Mori needs to interrogate the drug dealer who's been pushing Zola's opium in Old Market, but he was hacked to pieces right in front of them! What's a little death when a Zombie Maker owes you a favor?"--Back cover.